Pengembangan instrumen penilaian praktikum kimia fisik berbasis Keterampilan Generik Sains (KGS) yang valid, praktis dan efisien - Hardin Hardin; Sumiati Side (Seminar Nasional LP2M UNM, 2019)
This research is a development research focused on developing assessment instruments for Physical Chemistry based on generic science practicum (KGS) which include the development of pre-practicum assessment instruments, practicum assessment instruments, practicum report assessment instruments and affective assessment instruments. This study aims to obtain a valid effective and practical KGS-based practicum assessment tool. The research achieved through the activity plan stages includes: (1) theoretical studies, (2) preparation of assessment instruments, (3) validation of assessment instruments and (4) trial of assessment instruments. The KGS-based assessment tool developed was validated by two experts and then revised so that a valid device was obtained. Limited testing and implementation was carried out in the Department of Chemistry, FMIPA, Makassar State University with 60 students. The results showed that the assessment instruments developed after validated validation performed with the validation coefficients of the contents of each device were: pre-practicum assessment instruments, practical process assessment instruments, report assessment instruments, and affective assessment instruments with coefficient values, respectively validation of contents 1.00, 0.88, 1.00, 0.88. The assessment instrument was declared practical because most aspects were responded positively by the assistant. The assessment instrument is declared effective because it has met the effectiveness criteria, with the results: The overall score of the practitioner is in a very good category, Assistant activities and activities are fulfilled.